2013
DOI: 10.1891/0886-6708.vv-d-12-00019
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Victimization Risk: Exploring the Role of Deviant Lifestyles

Abstract: Although research over the past few decades has illustrated that gender is a significant predictor of victimization, there has been less attention toward explaining these differences. Furthermore, there has been little attention given to how offending and other deviant behaviors contribute to victimization risk for males and females. This is surprising considering that offending, particularly violent behavior, is highly correlated with victimization risk and that males are more likely to offend than females. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…These results are somewhat consistent with those of prior studies. For example, males’ substance abuse (e.g., drug use and heavy drinking) is linked to their repeat victimization, but females’ substance abuse is not (Ruback et al, 2014; Zaykowski et al, 2013). Property offending experience is linked to property victimization, to which females are more vulnerable (Wittebrood & Nieuwbeerta, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These results are somewhat consistent with those of prior studies. For example, males’ substance abuse (e.g., drug use and heavy drinking) is linked to their repeat victimization, but females’ substance abuse is not (Ruback et al, 2014; Zaykowski et al, 2013). Property offending experience is linked to property victimization, to which females are more vulnerable (Wittebrood & Nieuwbeerta, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Some work has recognized how childhood victimization creates distinctly gendered lifestyles distinguished by mental health issues, substance abuse, and intimate partner violence (Desai et al, 2002;Salisbury & Van Voorhis, 2009;Simons & Whitbeck, 1991). Within the general strain literature, there is also evidence that females tend to experience self-directed emotions like fear and anxiety, as well as overall higher levels of depression, especially over time, and tend to internalize their responses, whereas males may be more prone to feelings of hopelessness and expressing frustration in an other-directed criminal manner (Broidy, 2001;Campbell, 1993;Zaykowski & Gunter, 2013). This literature suggests that potentially estimating the integrated theoretical model separately for males and females may prove beneficial in exposing gender differences in when and under what conditions theoretical variables apply (Daigle et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, little empirical studies have been done along this line to support this assertion. For instance, Zaykowski and Gunter [40] in a study revealed that sex is a significant predictor of victimization but further posited that less attention has, however, been given to the differences.…”
Section: Discussionmentioning
confidence: 99%